Clinical and morphological myocardial changes in patients with post-COVID-19 syndrome - S. V. Mayrina; I. A. Makarov; L. B. Mitrofanova; M. S. Vonsky; A. L. Runov; K. A. Papko; O. M. Moiseeva (Российский кардиологический журнал, 2023)
Aim. To characterize the clinical manifestations and myocardial morphological changes in patients with cardiovascular complications of post-Covid syndrome.Material and methods. A total of 38 patients (Group I) with cardiac symptoms in the post-COVID-19 period underwent endomyocardial biopsy (EMB). Patients from group I were divided into 2 subgroups depending on the presence of morphologically verified myocarditis. For morphological comparison, group II was formed (41 patients without COVID-19 and with EMB performed before 2019). Group II was also divided into two subgroups with and without morphologically verified myocarditis. In addition to the analysis of clinical and paraclinical data, a histological and immunohistochemical study of myocardial tissue was carried out with anti-CD3, CD68, CD16, HLA-DR, MHC1, C1q, enterovirus VP1, SARS-CoV-2 spike protein, ACE2, Ang1, von Willebrand factor, VEGF antibodies, as well as a PCR of myocardial tissue after reverse transcription. Additionally, an immunofluorescent study of myocardial tissue was performed using antibody cocktails to SARS-CoV-2/ CD16 spike protein, SARS-CoV-2/CD68 spike protein, CD80/CD163. Statistical processing was performed using the NumPy, SciPy, Pandas and Matplotlib libraries in the Python programming language.Results. Among patients in group I, 65% had morphologically verified lymphocytic myocarditis (subgroup 1, n=29). Other 35% of patients had no signs of myocardial inflammation (subgroup 2, n=9). The comparison group (group II) included 33 patients with myocarditis (80%) and 8 patients (20%) without it. There was a pronounced expression of CD68+ macrophages in the myocardial tissue in patients with postCOVID-19 syndrome in comparison with group II, both with morphological criteria for myocarditis (p=0,014) and without it (p=0,007), mainly due to M2 macrophages. More pronounced expression of CD68+ macrophages was observed when EMB was performed at earlier stages. If SARS-CoV-2 spike protein was detected in group I on the endothelium and inflammatory infiltrate by the immunohistochemistry, PCR of myocardial tissue for SARS-CoV-2 (n=5) was performed, which did not reveal SARS-CoV-2 particles in any of the analyzed samples.Conclusion. Cardiac symptoms of post-COVID-19 syndrome are caused by myocardial remodeling, including in patients without morphologically verified myocarditis. The direct involvement of SARS-CoV-2 in the development of myocarditis in the post-acute period of COVID-19 has not been proven.